W sprawie „dekalogu” etyki politycznej liberalnej demokracji - Paradowska, Wiera; Paradowski, Ryszard (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2006)
The issue of morality in politics has been bothering political scientists since time immemorial. Throughout all this time attempts have been made to create a system of political ethics. These attempts have mainly been characterized by the tendency to make this ethical system universal (in conformity with a controversial assumption that it is possible – and indispensable – to offer a single, commonly observed ethical system) on the one hand, and by failing to consistently distinguish political norms of ethics from those of other kinds on the other. The proposal of a system of ethical norms presented below is based on the Judaic- Christian Decalogue. What is significant though, is that it only concerns the form – in particular the first ‘commandment’ is an unsurpassable (yet not the only one feasible) formula to combine the actually antinomic fundamental values; in terms of the content the ethics of liberal democracy (including political ethics) is a contradiction of the Decalogue. It should be pointed out that the fact that the liberal-democratic ‘decalogue’ is written in the first person singular is by no means a coincidence; and this is so because unlike in authoritarian ethics, where the system of norms comes from the giver who is not actually subjected to them, liberal-democratic ethics (both the political and ethical aspects) does not distinguish between the givers of the norms and the remaining subjects obligated to observe the norms they did not make themselves. Also, the list of norms presented may be considered incomplete, and this is actually the case. The same concerns the Judaic-Christian Decalogue also, in fact it is only the first commandment that is not accidental, the one that provides a key to the interpretation of the entire ethical system; in the ‘old’ decalogue the key is the principle of rules and obedience, in the present one – the principle of mutual acknowledgement of both parties’ equal status.
On the ''Decalogue'' of Political Ethics and Liberal Democracy